Assessment of the Structure, Conduct and Performance of Timber Markets in Southwest, Nigeria - Falana, A. R.; Azeez, I. O.; Omotayo, F. O. (NIU Journal of Humanities; Vol 10 No 4 (2025): NIU Journal of Humanities, Vol. 10 No. 4, December 2025, 2025)
The timber industry in Southwest Nigeria plays a vital role in socio-economic development, yet constrained by inadequate access to reliable and timely market information. This study assessed the structure, conduct and performance of timber marketing business in Southwest, Nigeria with a view to improve the performance of timber market in the region. Primary data were obtained from timber marketers across the six states of Southwest Nigeria, using structured questionnaires. Data were analysed using descriptive statistics, and the result was presented using tables and charts. Findings revealed that there was more male gender (62.8%) than female gender (37.2%) in timber marketing business in the region. The result of the ages of the respondents showed that 27.7% of the respondents were between the ages of 41-50, 26% were 51-60 years, 19.2% were 21-30, 16.1% were between 31-40 while 7.3% and 3.4% respectively of the respondents ages ranged between 60-70 years and above 70 years. There are diverse in size, specialisation, and market reach, with most operating through traditional marketing channels. Most timber marketers belonged to group of association and the association are paying vital roles in assisting their members. The Southwest Timber market is monopolistic in nature. It is recommended that effective Timber Marketing Information System be developed to enhance performance of timber marketing in Southwest, Nigeria in order to giving an easy access to vital timber marketing information. Keywords: Assessment, Structure, Conduct, Performance, Timber market, Southwest, Nigeria